Trans inclusivity through a conservative lens : News framing analysis on Fox News articles discussing transgender rights in the 2010's - Linnakoski, Lotta (My University, 2024)
This thesis examines conservative news outlet Fox News and its discourse in news about the transgender community. Furthermore, it seeks to discover, whether having a liberal or conservative president influences news discourse. This thesis analyzes text elements, such as depictions, metaphors, and word choices by utilizing framing theory, which was popularized by Erving Goffman. I also benefit from the Surplus visibility theory by Daphne Patai. The analyzed materials consist of six articles published during Barack Obama’s presidency and six articles published during Donald Trump’s presidency, the years of publication ranging from 2013 to 2019. The articles discuss transgender inclusivity and access in sports and public spaces. I examine the articles from three points of view: depictions, presentations of otherness, and the variety of voices included in the article. I argue that heteronormativity is a persistent element in conservative news discourse, regardless of the political values of the incumbent president. Transgender people were generalized more in the Trump era articles than those of Obama’s presidency and provided slightly more one-sided perspectives. Therefore, I argue that the news discourse of Fox News is affected by not only the context of time, but also the political values of the incumbent president.
Keywords: framing, news framing, transgender rights, conservatism, heteronormativity, Fox News